Evaluation of the social and economic impact of extreme weather events in people living with HIV in KwaZulu-Natal, South Africa (S3E project): Protocol for a mixed-method study - Saeideh Babashahi; Kingsley Orievulu; Ekeminiabasi Eyita-Okon; Dominic Kniveton; Collins Iwuji (PLoS ONE, 2025)
The impacts of extreme weather events (EWEs), such as droughts and floods, continue to be felt inequitably and disproportionately, with vulnerable communities experiencing diverse effects. While more is known about the direct impacts of EWEs on the general population, there is limited quantified evidence regarding the indirect socioeconomic impacts of climate-driven EWEs on vulnerable sub-populations such as people living with HIV (PLHIV). Globally, South Africa has the largest number of PLHIV, who by the nature of their medical needs and the stigma around their disease burden, have different vulnerability profiles to the wider population. KwaZulu-Natal province, which recorded the second-highest burden of HIV in South Africa, has been hit hard by recurrent floods in recent years. This study aims to evaluate the social and economic impacts of recent floods on PLHIV in the province and co-develop a priority list of policy interventions that would address and minimise flood impacts among PLHIV. This study involves three objectives, and a combination of qualitative thematic analysis and economic assessment will be applied to investigate the socioeconomic impacts of the recent floods in PLHIV across two rural districts in South Africa. The study will apply a mixed-methods exposed-unexposed approach to assess the impacts of recent floods on PLHIV concerning treatment adherence, healthcare use, out-of-pocket expenses, coping mechanisms, work productivity loss, and other economic losses. An equity impact analysis will be conducted to examine how the socioeconomic impacts of floods are distributed disproportionately within the study sample. A priority list of policy interventions will be co-developed to minimise the impacts of floods using participatory research methods and multi-criteria decision analysis. Using a novel mixed-methods approach, this study contributes to understanding the social and economic impacts of recent floods on PLHIV and co-produces a list of adaptive and mitigation policy interventions to address these impacts.